Dual‐band reflected beam steering with single‐layered focusing anisotropic metasurface. Issue 9 (15th April 2019) - Chen, Jiaqing; Zhao, Yongjiu; Xing, Lei; Dai, Huijuan; Chen, Xiaofeng; Ge, Yue
Abstract : Phase gradient metasurface (PGM) is capable of realising anomalous wave deflection, while focusing metasurface is widely adopted in converging electromagnetic (EM) waves through phase compensation. Here, a single‐layered focusing anisotropic metasurface (FAM) for dual‐band reflected beam steering is proposed. The anisotropic metasurface is composed of modified Jerusalem cross‐structures with which reflected waves can be focused and deflected simultaneously. Furthermore, the distributions of reflection phase required in two frequency bands can be controlled independently by adjusting the dimensions of the cells along two orthogonal directions. To verify the proposed structure, a prototype with a size of 260 × 260 mm is fabricated, assembled, and measured. Good performances have been achieved in both simulation and measurement results, which agree with theoretical predictions. The measured results indicate that reflected waves generated by the FAM can be deflected to −42° with a gain of 17.5 dBi and −30° with a gain of 20.5 dBi at 5.7 and 10 GHz, respectively.